The role of the midcingulate cortex in monitoring others' decisions - Apps, Matthew A.; Lockwood, Patricia L.; Balsters, Joshua H. (Frontiers in Neuroscience, 2013)
A plethora of research has implicated the cingulate cortex in the processing of social information (i.e. processing elicited by, about, and directed towards others) and reward-related information that guides decision-making. However, it is often overlooked that there is variability in the cytoarchitectonic properties and anatomical connections across the cingulate cortex, which is indicative of functional variability. Here we review evidence from lesion, single-unit recording and functional imaging studies. Taken together, these support the claim that the processing of information that has the greatest influence on social behaviour can be localised to the gyral surface of the midcingulate cortex (MCCg). We propose that the MCCg is engaged when predicting and monitoring the outcomes of decisions during social interactions. In particular, the MCCg processes statistical information that tracks the extent to which the outcomes of decisions meet goals when interacting with others. We provide a novel framework for the computational mechanisms that underpin such social information processing in the MCCg. This framework provides testable hypotheses for the social deficits displayed in autism spectrum disorders and psychopathy.